Pattern of skin cancer in Saudi patients at King Abdulaziz Medical City in Riyadh, Kingdom of Saudi Arabia between 2005 and 2015: A retrospective study - Sultan Al Qahtani; Rawan Aldahash; Najd BinManie; Mohammed Al Assiri (Wolters Kluwer Medknow Publications, 2020)
Background: Skin cancer is one of the most common among white-skinned individuals. Its prevalence depends on geographic and ethnic variations. The pattern of skin cancer in Saudi patients per province is not well-established. Purpose: This retrospective study evaluated the pattern of skin cancer among Saudi patients from Riyadh area who have visited King Abdulaziz Medical City (KAMC), Riyadh, Saudi Arabia, between the years of 2005 and 2015. Methods: Data from 300 cancer patients were collected from KAMC and analyzed with respect to age, sex, cancer type, and cancer location. Results: Except for mycosis fungoides (MF), all other studied skin cancer types were more common in males as compared to females (1.56:1). Among the study population, the majority of skin cancer cases were seen in patient who aged more than 40 years old (86%) with the highest rate to be among those who are between 60 and 79 years old. Among all cases, the pattern and ratio of various skin cancers were as follows: Basal cell carcinoma (BCC) (45.7%), squamous cell carcinoma (SCC) (14.7%), MF (7.3%), and malignant melanoma (MM) (7%), followed by sebaceous adenocarcinoma (SC), Kaposi sarcoma, and dermatofibrosarcoma protuberance each of 4.3%. With respect to cancer location, 141 cases were located on the face (46.95%), 46 on the hips and lower limbs (15.26%), 44 on the chest and abdomen (14.8%), 28 on the scalp and neck (9.29%), 21 on the shoulders and upper limbs (6.95%), and 17 were unspecified. Conclusion: Among Saudi patients with skin cancer in the central region of the Kingdom of Saudi Arabia (KSA), BCC and SCC were the most common cancers, followed by MF and MM. Further studies are needed to fully determine common risk factors among these and future cases.